Assessing the Healthcare Service Quality in a Smart City in Eastern India - Samal et al., Dr. Ansuman (International Journal of Advanced Science and Technology, 2020)
Quality is the new buzzword in the modern-day business sector, as fierce competition is going on in this volatile market whereeveryone wants a larger pie than the rest. In the era of globalization, when the products are getting generalized and services personalized, it is the classic quality that marks the difference. As healthcare is the backbone of a society that helps to maintain a sizable and competent pool of human resources, it is the need of the hour to carefully assess and take precautionary measures to ensure quality in its processes. In this regard, the case of Bhubaneswar has been taken which is the capital and largest city in the state of Odisha, India.Recently, it was ranked as the first-mostsmart city in the country under the much ambitious smart city mission launched by the ministry of urban development. We have taken the samples from the three renowned private teaching hospitals situated in the city to assess the perception of the patients towards the healthcare services available. As of general conception, the private hospitals are superior to the public hospitals and the teaching hospitals provide superior quality than the nonteaching ones, we have chosen the private teaching hospitals for the study. The SERVQUAL model was used through a questionnaire to capture the perceptionexpectation scores in a seven-point scale.Based on the evidences and stimulated by the feedbacks, some recommendations have been made to improve upon the service quality.